1998
DOI: 10.1149/1.1838783
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Temperature Solid Oxide Fuel Cells Using a New LaGaO3 Based Oxide Ion Conductor: I. Doped as a New Cathode Material

Abstract: LaGaO,-based perovskite oxides doped with Sr and Mg exhibit high ionic conductivity over a wide range of oxygen partial pressure. In this study, the stability of LaGaO,-based oxide was investigated. The LaGaO,-based oxide was found to be very stable in reducing, oxidizing, and CO2 atmospheres. Solid oxide fuel cells (SOFCs) using LaGaO,-based perovskite-type oxide as the electrolyte were studied for use in intermediate-temperature SOFCs. The power-generation characteristics of cells were strongly affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(107 citation statements)
references
References 4 publications
1
106
0
Order By: Relevance
“…In contrast, Sm 0.6 Sr 0.4 CoO 3 shows reasonably high stability and surface activity. 32 Recently, many new materials have been reported that show high activity and stability, such It is also reported that the layered interface of LaCoO 3 /La 2 CoO 4 shows extremely high activity to oxygen dissociation. 35 , 36 To gain a fundamental understanding of the ORR mechanism on these materials, several techniques are being used, such as conductivity relaxation 37 and in situ 38 and ex situ 39 oxygenisotope exchange.…”
Section: Increasing Cathode Catalytic Activity and Conductancementioning
confidence: 99%
“…In contrast, Sm 0.6 Sr 0.4 CoO 3 shows reasonably high stability and surface activity. 32 Recently, many new materials have been reported that show high activity and stability, such It is also reported that the layered interface of LaCoO 3 /La 2 CoO 4 shows extremely high activity to oxygen dissociation. 35 , 36 To gain a fundamental understanding of the ORR mechanism on these materials, several techniques are being used, such as conductivity relaxation 37 and in situ 38 and ex situ 39 oxygenisotope exchange.…”
Section: Increasing Cathode Catalytic Activity and Conductancementioning
confidence: 99%
“…Among innumerable oxygen ion conductors viz. ceria, La-gallate (Ishihara et al, 1998) (Manner and Ivers-Tiffee, 1991) are the promising candidates. Fully stabilized zirconia offers the best choice of electrolyte having satisfied criteria of conductivity, chemical stability, durability, etc.…”
Section: Electrolytementioning
confidence: 99%
“…There are basically two approaches to solve this difficulty. One is to employ new electrolyte materials possessing higher ionic conductivity, such as CeO 2 and Bi 2 O 3 [2][3][4]. However, the redox behavior of the former and the insufficient strength and toughness of the latter remain to be solved before they can be practically utilized.…”
Section: Introductionmentioning
confidence: 99%